2023
DOI: 10.1111/aas.14301
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of acute postoperative pain after total knee and hip arthroplasty: A systematic review

Anders H. Springborg,
Lasse Visby,
Henrik Kehlet
et al.

Abstract: BackgroundIdentifying patients at high risk of acute postoperative pain after total knee or hip arthroplasty (TKA/THA) will facilitate individualized pain management and research on the efficacy of treatment options. Numerous studies have reported that psychological patient factors may influence acute postoperative pain, but most reviews have focused on chronic pain and functional outcomes. This systematic review aims to evaluate which psychological metrics are associated with acute postoperative pain after TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Previous studies have also shown that PCS was significantly associated with both acute and chronic pain after surgery. 39 , 40 In addition, the emerging pattern of findings supports the view that the relationship between PCS and pain experience could be likely bidirectional, as the experience of pain could give rise to catastrophic thinking, contributing to adverse pain outcomes. 41 It has been shown that PCS was associated with greater acute pain intensity and increased risk of persistent pain after cesarean section.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have also shown that PCS was significantly associated with both acute and chronic pain after surgery. 39 , 40 In addition, the emerging pattern of findings supports the view that the relationship between PCS and pain experience could be likely bidirectional, as the experience of pain could give rise to catastrophic thinking, contributing to adverse pain outcomes. 41 It has been shown that PCS was associated with greater acute pain intensity and increased risk of persistent pain after cesarean section.…”
Section: Discussionmentioning
confidence: 56%
“…The current and earlier literature indicates that preoperative pain predisposes to a complicative postoperative pain experience. Moreover, personal characteristics such as distinct pain catastrophizing, anxiety, and habits such as smoking or an elevated body mass index (BMI) can lead to complex pain scenarios and increased incidence of chronic pain [25][26][27][28][29]. In particular, smoking and preoperative anxiety were found to be independent risk factors for postoperative pain in anophthalmic surgery [30].…”
Section: Discussionmentioning
confidence: 99%